Characterization of the international network FAIR 202 of provenance and progeny trials of cork oak on multiple sites for further use on forest sustainable management and conservation of genetic resources. - Varela, Maria Carolina (2017)
The international network of provenance and progeny trials was established in 1998 benefiting from homogeneous plant raising and standardize experimental design. The trials include 34 provenances that are being characterised by several teams. France 2008. Provenance PT 23 and PT+ES 25 had the lowest survival rate. In 2008 the mean height was 48.73 cm and the form keeps plagiotropic. Italy- Sardinia, 2010 - The average mortality was 7%. Mean height and trunk DBH over cork were respectively 273 and 5.1 cm. MO I-2, TU II, ES 4-CR are above mean on height (302-309 cm), and the Italian provenances are under mean (237-249cm). Italy- Roccarespampani, Lazio- The mortality is about 45% and it is the only plantation site where the French provenance FR3 has a growth above mean. Portugal. Results show significant differences among populations on survival and growth. The Moroccan provenances show good adaptive characteristics in terms of growth, vigour and stem form. Italian provenances present lower height but higher survival. The overall mortality is around 26%. The highest growth is being observed in the Moroccan provenances and French ones showed lowest survival. Provenances and plantation sites are characterised for rainfall regime. The provenances Morocco MA27 and Tunisia TU33 that are from sites of high rainfall are among the best on growth at sites of considerable more xerothermic climate. If persistent at older age these results indicate that fast adaptation of cork oak populations to cope with climate changes leading to drier and warmer conditions seems possible.